一种纳米级凹凸棒加工用研磨装置 (2024)
本发明公开一种纳米级凹凸棒加工用研磨装置，处理箱内上方设有粉碎机构，粉碎机构下方设有粗研磨机构，粗研磨机构中通过回料管设有螺旋回料轴，回料管下方的处理箱内设有升降筛选机构，处理箱下方设有研磨箱，处理箱下方与研磨箱之间通过连接机构设有一级精磨筒，一级精磨筒底端设有纳米筛网，一级精磨筒上设有超声波机构，一级精磨筒下方设有二级精磨机构；本发明通过创新性粉碎和升降调节的回料管结构使得物料可直接加入原料初步粉碎后往复粗磨加工，配合多级超声振动研磨结构加工制得的纳米凹凸棒粒径均匀且可控，同时超声振动研磨有效解决传统装置转动研磨粒径难控、加工时间长的缺陷，加工速度快且加工的纳米粒径均匀可靠。 The grinding device is characterized in that a smashing mechanism is arranged on the upper portion in a treatment box, a coarse grinding mechanism is arranged below the smashing mechanism, a spiral material returning shaft is arranged in the coarse grinding mechanism through a material returning pipe, a lifting screening mechanism is arranged in the position, below the material returning pipe, in the treatment box, and a grinding box is arranged below the treatment box; a first-stage accurate grinding barrel is arranged between the lower part of the treatment box and the grinding box through a connecting mechanism, a nano screen is arranged at the bottom end of the first-stage accurate grinding barrel, an ultrasonic mecha